L’esclave du ms. H.6 et l’anthropologue romancier : In an Antique Land d’Amitav Ghosh, une utopie de l’archive - Claudine Le Blanc (Amnis)
As Subaltern Studies, Indian postcolonial studies developed a textual criticism of archival documents which soon met literature: as early as 1992 in Volume VII a study of the correspondence of a Jewish merchant of the twelfth century ("The Slave of MS. H.6") was published by the young anthropologist and novelist Amitav Ghosh Bengali, who published the same year In a Antique land, an account of his fieldwork in Egypt, inspired by the same correspondence. But neither the article nor the story does mention one the other: this is not a relation of succession, but exclusion which orders both texts, leading to the abandonment by Ghosh of history in favor of literature. This article examines this split writing of the archive that enables the reader to consider In an Antique Land as a fiction of archive, not only as a fictionalization of historiographical sources, but as an art of multiplying and crossing plots in a set of fragmentation and meeting which transforms experience into novel – the novel of the quest of a past that makes sense to the present.